Aberrant expression of the S1P regulating enzymes, SPHK1 and SGPL1, contributes to a migratory phenotype in OSCC mediated through S1PR2 - Patmanathan, Sathya Narayanan (NATURE PUBLISHING GROUP, 2020)
10.1038/srep25650